Indonesian Language Teachers’ Perceptions of Project-Based Learning (PjBL) Implementation - Awaliyah, Mia (COPE: Caraka Olah Pikir Edukatif, 2026)
The Project-Based Learning (PjBL) approach is one of the main strategies in the implementation of the Independent Curriculum, as it emphasizes collaborative, contextual, and problem-solving-oriented learning. This study aims to describe the perceptions of Indonesian language teachers toward the implementation of PjBL and to identify the challenges and needs for strengthening its application in schools. The research employed a qualitative descriptive approach, with data collected through questionnaires and interviews involving Indonesian language teachers from six public and private junior high schools in Bantul Regency. The results indicate that most teachers have a good understanding of the concepts and stages of PjBL (82%) and demonstrate a relatively high level of readiness (73%) in its implementation. However, the practical application in the classroom remains constrained by limited time, learning facilities, and institutional support. These challenges have encouraged teachers to adapt PjBL contextually, for example, through simple projects based on local culture. The findings also reveal that 91% of teachers require further practical training to design, implement, and assess project-based learning effectively. The implications of this study highlight the importance of strengthening teacher capacity through practice-oriented training, the provision of adequate learning facilities, and the development of collaboration among schools, education authorities, and local communities to achieve effective, sustainable, and contextually relevant implementation of PjBL in Bantul Regency.